Chemical Perturbation of Chloroplast-Related Processes Affects Circadian Rhythms of Gene Expression in Arabidopsis: Salicylic Acid Application Can Entrain the Clock - Philippou, Koumis; Davis, Amanda M.; Davis, Seth J.; Sánchez-Villarreal, Alfredo (Frontiers in Physiology, 2020)
The plant circadian system reciprocally interacts with metabolic processes. To investigate entrainment features in metabolic-circadian interactions, we used a chemical approach to perturb metabolism and monitored the pace of nuclear-driven circadian oscillations. We found that chemicals that alter chloroplast-related functions modified circadian rhythms. Both vitamin C (vitC) and paraquat altered circadian period in a light-quality dependent manner, whereas rifampicin lengthened circadian period. Salicylic acid (SA) increased oscillatory robustness and shortened period. This latter effect of SA was attenuated by sucrose addition and was also gated, taking place during the first half of the subjective day. Period lengthening or shortening by these chemicals was correlated to their inferred impact on photosynthetic electron-transport activity and the redox state of plastoquinone (PQ). Based on these data, and on previously published circadian effects that alter the redox state of PQ, we propose that the photosynthetic electron transport and the redox state of PQ participate in circadian periodicity. Moreover, coupling between chloroplast-derived signals and nuclear oscillations, as observed in our chemical and genetic assays, produces traits predicted by previous models. SA signaling or a related process forms a rhythmic input loop to drive robust nuclear oscillations in the context predicted by the zeitnehmer model previously developed for Neurospora. We further discuss the possibility that Electron Transport Chains (ETCs) are part of this mechanism.